Accession of the Crimea Territory to Russia: the Crimea’s Inestimable Value - I. V. Mikheeva; A. S. Loginova; A. V. Skiperskikh (Сравнительная политика)
The issue is devoted to the Crimea and Sevastopol city accession to the Russian Federation. The economic effects of the Crimean territorial policy of the Russian government are considered. The assumption is made that the occurrence of the Crimea in the economic and legal space of the Russian Federation has included signifi cant investment. Meanwhile, it is worth far less than the prospect of Crimea to share the fate of modern Ukraine. The article considers the political consequences of Crimea's integration into Russia. From the authors’ point of view this integration was an important event in world politics that signifi cantly changed the fi eld of international relations and «rules of the game». It has been revealed how events in Crimea have changed the vector of development of Russian policy in the context of domestic life and in the international community. It is shown that the integration of the Crimea becomes an important fi gure in Russian political discourse, linking the foreign and domestic policies of modern Russia. This underlines the seriousness of the Crimean agenda in the public consciousness. The accession of Crimea and Sevastopol City into the Russian Federation has allowed the ruling elite of modern Russia make the best use of opportunities for their own legitimization.